Finding common ground : enhancing interaction between domestic and international students : final report. - Arkoudis, Sophie; Yu, Xin; Baik, Chi; Chang, Shanton; Lang, Ian; Watty, Kim; Borland, Helen; Pearce, Amanda; Lang, Josephine (Australian Learning and Teaching Council, 2010)
A feature of higher education in Australia is the cultural diversity of the student population. The absolute number of international students studying in Australian universities has increased dramatically in the last decade, as has the number and diversity of countries represented among the student populations of our universities. This diversity provides great potential for all students - both international and domestic - to interact with peers from different cultural and linguistic backgrounds. Evidence suggests however that successful peer interaction cannot be assumed simply because students share a campus or a course. So, what more can be done to harness the potential of student diversity? In particular, in what ways can university teaching promote interaction between students from diverse cultural and linguistic backgrounds? These questions were investigated through this 2008-10 project supported by the Australian Learning and Teaching Council (ALTC). The project explored the benefits of, and obstacles to, interaction among students from diverse cultural and linguistic backgrounds. The project also sought to identify examples of practice that were successfully enhancing such interactions within Australian university teaching and learning environments. A key outcome was the development of a six-dimension conceptual framework, the Interaction for Learning Framework. [p.1, ed]